"Participation, satisfaction, perceived benefits, and maintenance of behavioral self-management strategies in a self-directed exercise program for adults with arthritis". (February 2017) - Sharpe, Patricia A.; Wilcox, Sara; Schoffman, Danielle E.; Baruth, Meghan
Highlights: Participants reported high exposure to exercise program materials and participation in setting goals, following a plan, and self-monitoring. Self-monitoring declined over nine months, but the majority still reported at least some success in following their plan. Adults with arthritis perceived a variety of benefits from a self-directed exercise program. The majority of participants rated the program as good or excellent during both the initial period and the maintenance phase. Abstract: A process evaluation was conducted in conjunction with a controlled trial of a self-directed exercise program among people with arthritis to describe the program's reach; self-management behaviors, exposure to materials, program perceptions, satisfaction, and perceived benefits; compatibility with targeted participants' needs; and maintenance. Participants (n = 197) were predominantly white, middle-aged, college-educated women. At 12 weeks, 73.2% had read ≥90% of the program materials (at nine months >70% had "occasionally" or "often" looked back over each of the five parts of the materials); 63.3% had set goals (52.5% at nine months), and 83.9% had "some" or "a lot" of success following their plan (64.2% at nine months), while 90.4% rated the program "good" or "excellent" (87.5% at nine months). At 12 weeks, the majority (89.3%) used written logs to self-monitor (mean = 9.3 logs); by nine months, >70% never kept logs. Most (>80%) rated twelve of thirteen program components as helpful, and 98.6% would recommend the program. From 38% to 62.4% endorsed each of eight program benefits, with small declines of ≤9% at nine months. Qualitative response identified ways the program met and did not meet expectations. The main program compatibility issue was targeting all adults with arthritis, while featuring older adults in materials.